A case of young diabetes and parasuicide. (18th September 2018) - Lodha, Sailesh; Das, Liza; Ramchandani, Ghanshyam das; Bhansali, Anil
Abstract : Wolfram syndrome is a rare monogenic cause of juvenile onset diabetes mellitus. It is a non-autoimmune, insulin-deficient state with concurrent or consequent optic atrophy. Here we depict the case of a 16-year-old young girl afflicted with this condition, who presented with parasuicide on a background of depressive disorder. The aetiology of this presentation was attributable to multiple physical ailments and a genetic predisposition conferred by the disease-causing mutation for which she tested positive. She was managed with intensive insulin therapy and specific psychotherapy. Her case highlights the importance of recognising and addressing these comorbidities associated with Wolfram syndrome, so as to curtail disastrous consequences.